Consistency of online consumers' perceptions of posted comments: An analysis of TripAdvisor reviews - Khoo, Foo Sheng*; Teh, Phoey Lee *; Ooi, Pei Boon * (Universiti Utara Malaysia, 2017)
Ratings and comments play a dominant role in online reviews. The question, thus, arises as to whether or not there is any consistency in consumer perception of the reviews, and how future choices might be influenced. We analysed 2000 comments of 20 different hotels posted on TripAdvisor to determine if the comments posted by previous guests of a hotel influence the decisions of potential guests. Two hundred human raters were asked to consider 20 reviews and to rate a hotel based on the reviews. The Cohen Kappa coefficient was used to evaluate the degree of agreement on the hotel quality as determined by the human raters and the star rating given by the original reviewer. The results showed a high consistency between the human raters’ evaluation and the reviewers’ star rating. This research reveals the importance of website feedback such as TripAdvisor in influencing consumer choice.